2020
DOI: 10.1016/j.ijpx.2020.100053
|View full text |Cite
|
Sign up to set email alerts
|

Xyloglucan based mucosal nanovaccine for immunological protection against brucellosis developed by supercritical fluid technology

Abstract: Vaccines delivered via the mucosal route have logistic benefits over parenteral or intramuscular vaccines as they offer patient compliance. This study presents the first intranasal, controlled release, subunit nanovaccine comprising mucoadhesive tamarind seed polymer (xyloglucan) based nanoparticles produced using an efficient, environmentally compatible, and industrially scalable technique: rapid expansion of supercritical solution. The nanovaccine formulation aimed against brucellosis comprised xyloglucan na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Additionally, the inclusion of xyloglucan in the formulation led to a significant decrease in sIgA levels in the pulmonary mucus. A recent independent study showed that a nanovaccine containing Quillaja saponin and Brucella abortus S19 LPS elicited a mixed Th1/Th2 type of immunity in BALB/C mice when administered intranasally [ 27 ]. However, the study found a stronger IgG2a response than IgG1, which differed from the findings in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the inclusion of xyloglucan in the formulation led to a significant decrease in sIgA levels in the pulmonary mucus. A recent independent study showed that a nanovaccine containing Quillaja saponin and Brucella abortus S19 LPS elicited a mixed Th1/Th2 type of immunity in BALB/C mice when administered intranasally [ 27 ]. However, the study found a stronger IgG2a response than IgG1, which differed from the findings in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The Brucella smooth LPS is several hundred times less toxic and non-pyrogenic compared to other lipopolysaccharides [ 24 ], making it a potential alternative vaccine. Its utility in protecting against brucellosis has been demonstrated [ 24 , 25 , 26 , 27 ]. Xyloglucan is a natural plant polysaccharide and non-toxic food additive with mucoadhesive and immunopotentiation properties [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…While Brucella LPS was weakly immunogenic, when B. abortus LPS-loaded XG NPs were administered nasally to Balb/c mice, higher systemic and mucosal IgG antibody levels and mucosal IgA were induced. Increased immunogenicity was associated with a greater mucoadhesion force of the XG and the LPS-XG NPs compared to the LPS alone, as well as the ex vivo retention of LPS-XG NPs over 24 h in goat mucosa [ 141 ].…”
Section: Mucoadhesive and Mucopenetrating Polymer-based Adjuvantsmentioning
confidence: 99%
“…Other examples include the use of PLGA NPs encapsulating antigens and adjuvants to treat leishmaniasis [17], a coordination polymer formed between Manganese (Mn 2+ ) and an organic ligand, meso-2,6-diaminopimelic acid, encapsulating ovalbumin for tumor therapy [18], xyloglucan (a tamarind seed-derived polymer) NPs encapsulating lipopolysaccharides from Brucella spp. as a mucosal vaccine against brucellosis that showed superior mucosal adhesive properties [19], and a peptide-polymer NP capable of transforming into nanosheets in an acidic pH, releasing the antigen to the cytoplasm for cancer therapy [20]. Different routes of administration were utilized depending on the nature of the polymeric delivery vehicle and antigenic component.…”
Section: Trends In Pharmacological Sciencesmentioning
confidence: 99%
“…Different routes of administration were utilized depending on the nature of the polymeric delivery vehicle and antigenic component. While certain vaccines elicited robust immune responses when administered intramuscularly or subcutaneously, other vaccines were more efficient when administered intranasally because they had excellent mucosal adhesive properties that promoted the activation of mucosa resident innate immune cells [15,19]. In all these examples, the use of a polymer led to either protective immunity or high levels of antibody production in vivo, showing that polymers are excellent components and carriers for vaccines.…”
Section: Trends In Pharmacological Sciencesmentioning
confidence: 99%